Cover Feature: Synthesis, Characterization and Electrochemical Properties of Polymers Based on Dithienothiophene and Bithiazole (Asian J. Org. Chem. 9/2020). Issue 9 (3rd September 2020) - Dikcal, Fatma; Topal, Sebahat; Unal, Murat; Ozturk, Turan
Abstract : 3, 5‐Dinonyl‐2, 6‐di(thiophene‐2‐yl)dithieno[3, 2‐b:2', 3'‐d]thiophene (M1) as a donor and 4, 4′‐dinonyl‐5, 5′‐di(thiophen‐2‐yl)‐2, 2′‐bithiazole (M2) as an acceptor were synthesized, and their polymers P1 and P2, respectively, were obtained via electropolymerization. A third polymer (P3), a co‐polymer of the monomers M1 and M2, was also synthesized through electropolymerization. Their electronic and capacitor properties were investigated, and EIS measurements indicated that P3 had the highest current density, having lower resistance. More information can be found in the Full Paper by Turan Ozturk et al.